The Misbegotten Child of Deep Ecology. (1st February 2004) - Avery, Stephen
Abstract : This paper offers a critical examination of efforts to use Heidegger's thought to illuminate deep ecology. It argues that deep ecology does not entail a non-anthropocentric or ecocentric environmental ethic; rather, it is best understood as offering an ontological critique of the current environmental crisis, from a perspective of deep anthropocentrism.